In silico study of the ErbB4 interactions with curcumin analogs - Azman, Putri Arsyadian; Abd Halim, Khairul Bariyyah (2015)
Curcumin (diferuloylmethane) is generally found as the major compound in rhizomes of turmeric plants Curcuma longa Linaeusas. Curcumin has been shown to inhibit cancer growth by means of inhibiting ErBB family members (ErbB1, Erbb2, ErbB3 and ErbB4). This family receptors often targeted for development of cancer therapeutics. Previously, curcumin has also been shown to selectively inhibit EGFR or ErbB1 in in vitro, in vivo as well as in silico studies. However, its inhibitive effect on ErbB4 has not been elucidated. The present study evaluated the efficacy of natural curcumin and its analogs as ErbB4 inhibitors using computational approach namely molecular docking and molecular dynamics simulation. These approaches have been used to investigate the interactions between ErbB4 with curcumin analogs. Our molecular docking simulation showed that among five ligands that were docked at the active site cavity of ErbB4, ligand D docked with the lowest binding energy which was -7.29 kcal/mol. Ligand D which was the lowest energy complex obtained from docking experiment was then further investigated using molecular dynamics simulations. Ligand D were quite well oriented in the binding pocket throughout the 10 ns simulations. Molecular docking and molecular dynamics (MD) simulation studies showed that curcumin could be embedded into the hydrophobic pocket of ErbB4 and form stable hydrogen bonding interactions mainly with residue LYS-59. In conclusion, we have explored the binding mechanism of curcumin binding to ErbB4. This work could offer useful insight for designing novel analogs of curcumin as potential ErbB family inhibitors in the future.